2008
DOI: 10.1080/18128600808685684
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Equations Analysis of Revealed and Stated Travel Mode and Activity Choices

Abstract: This study extends the structural equations model to incorporate both revealed and stated preference data to analyze activity-based travel behavior. The model is applied to examine the relationship between activities and mode choice on the data from the first wave of the panel study conducted for the Puget Sound Regional Council. It is found that the attitude toward comfort of travel, car requirement for job, and travel time are significant predictors for the mode choice decision. Comparing alternative decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…Often, consumers' choices are dependent on the outcome of prior decisions. Sakano and Benjamin (2008) analyzed mode choice for commute trips and activity choice on the way home, using a structural equations model; Sakano and Benjamin (2011) also analyzed mode choice to work and activity choice at the destination, again using a structural equations model. They found that when people decided to travel to work, mode choices and activity choices interacted.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Often, consumers' choices are dependent on the outcome of prior decisions. Sakano and Benjamin (2008) analyzed mode choice for commute trips and activity choice on the way home, using a structural equations model; Sakano and Benjamin (2011) also analyzed mode choice to work and activity choice at the destination, again using a structural equations model. They found that when people decided to travel to work, mode choices and activity choices interacted.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sakano et al [10] developed a structural equation model to check commuters' planning decisions on activities and patterns during a working day. Sakano et al [11] extended the structural equation model to analyze activity-based travel behaviors by combining displayed and stated preference data. Johansson et al [12] used indicators of attitudes and personality traits to form latent variables for inclusion in a standard discrete pattern selection model.…”
Section: Related Workmentioning
confidence: 99%
“…The first stated preference model was developed in the 1970s as a marketing research approach to obtain a better understanding of travel behaviour (Adler and Ben-Akiva, 1976;Davidson, 1973). More recently, discrete choice models based on stated preference methods have become a popular option among academics, governments and consulting companies to explore many aspects of transportation, including mode choice behaviour under different traffic management policies, devices and urban forms, and the relationship between business air travel and videoconferencing (Bhat, 1997;Fowkes and Preston, 1991;Hensher and Battellino, 1997;Lu and Peeta, 2009;McMillan, 2007;Sakano and Benjamin, 2008). Goodwin (1995) argued that the consideration of the differences among people is crucial to travel behaviour analysis.…”
Section: Introductionmentioning
confidence: 99%